A Latent Profile Analysis of Suicidal and Self-Injurious Behavior, Other Dysregulated Behaviors, and Borderline Personality Disorder Symptoms. Issue 4 (December 2015) - Selby, Edward A.; Gardner, Kathryn
Those with borderline personality disorder (BPD) exhibit many dysregulated behaviors, such as non-suicidal self-injury (NSSI), dysregulated eating, and substance use. The purpose of this study was to examine BPD symptoms and levels of these dysregulated behaviors with latent profile analysis, which allows for the empirical investigation of distinct behaviors patterns among those with BPD. A non-clinical student sample was screened for elevated BPD symptoms (N = 128, age = 18.75 years [SD = 1.05], 76.8% female) and used in mixture modeling analyses. Results supported five profiles from the sample, primarily distinguished by suicidality and NSSI: a low BPD-low dysregulated behavior profile, a low BPD profile with elevated suicidality, a low BPD profile with elevated NSSI, a high-BPD with low NSSI and somewhat elevated suicidality, and a high-BPD profile with high NSSI and low suicidality. Follow-up analyses indicated that other dysregulated behaviors did little to distinguish between those with high BPD symptoms. There were also important difference in motivational functions for NSSI between two of the profiles: those with high or low BPD symptoms who self-injured frequently. These findings are relevant to the ongoing debate about the existence of a NSSI disorder distinct from BPD.